Bovine manure and rock powder and their influences on the chemical characteristics of a Latossolo soil type (yellow oxisols) under butter kale (Brassica oleracea L. var. acephala) cultivation - Pereira, Micaela Benigna; Véras, Mário Leno Martins; Lima, Neriane Rodrigues de; Santos, Leandro Gonçalves dos; Dias, Thiago Jardelino (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Chemical soil quality is one of the factors more quickly affected by anthropogenic degradation processes and is one of the more important components for the development of agriculture. Thus, this study aimed to evaluate the effects of different doses of cattle manure and rock powder on the chemical characteristics of soil cultivated with butter kale. The treatments were arranged in five randomized blocks in a 4´4 factorial for the different doses of bovine manure (60, 120, 180 and 240 g/plant) combined with doses of rock powder (6, 12, 18 and 24 g/plant). Each block was composed of three plots, 18 m long and 1 m wide. The bed was composed of six portions, and each experimental plot consisted of 14 plants spaced at 0.40´0.40 m. At the end of the experiment, the following were analyzed: pH, organic matter, P, K, Na, Mg, exchangeable acidity, cation exchange capacity (CEC), sum of base and base saturation. The doses of bovine manure and MB-4 provided an increase in pH, organic matter, concentration of phosphorus, potassium, sodium, calcium, magnesium, exchangeable acidity, cation exchange capacity, sum of the base and saturation of the soil base. The doses of 240 g of cattle manure and 24 g of rock dust generated an increase in the chemical properties of the soil.